Segmental Odontomaxillary Dysplasia: Review of the Literature and Case Report - Riya M. Kuklani; Madhu K. Nair (International Journal of Dentistry)
Segmental Odontomaxillary Dysplasia (SOD) is an uncommon, nonhereditary, recently recognized developmental disorder affecting the upper jaw and related dental components. It is a rare condition of uncertain etiology that results in painless unilateral expansion of the posterior dentoalveolar complex, gingival hyperplasia, lack of one or both premolars in the affected area, delayed eruption of adjacent teeth and malformations of the primary molars. Radiographically, the affected bone is thickened and irregular in outline, with coarse trabecular pattern that is vertically oriented resulting in a relatively radiopaque granular appearance. Only a few cases have been reported in the English literature. Considering the rarity of the condition, we report a case of SOD in a pediatric patient who was followed up over a period of over two years. The clinical, radiographic, and histologic features are presented along with a review of the literature.